Länk och ekvivalens i en mångspråkig lexikografisk relationsdata bas - Winnerlöv, Jonas (Nordiske Studier i Leksikografi, 2001)
The paper presents a lexicographic system developed in a standard PC software and based on a multilingual relational database with a structure optimized for the electronic age. Equivalence is created on two independent levels, headword and example, on the basis of relational links between tables for selected pairs of languages. An additional leve! consisting of analytic bidirectional articles has been created in order ta handle culturally specific words and other categories, corresponding roughly to 5 percent of the lemmas, where equivalence cannot be obtained on the two first levels. These three modules are common fora variety of electronic and printed products, for instance a compact pocket dictionary, using a combination of first-level equivalence in simple word lists and analytic articles.